THE INFLUENCE OF SERVICE QUALITY, PRICE, AND PROMOTION ON SHOPEEFOOD CUSTOMER LOYALTY IN STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS MAKASSAR PUBLIC UNIVERSITY - Ribhi Awad; Anwar Ramli; Muhammad Ilham Wardhana Haeruddin; Amiruddin Tawe; Muhammad Ichwan Musa (Transpublika Publisher, 2023)
The emergence of online-based food delivery services has significantly transformed consumer behavior, especially in the context of the COVID-19 pandemic. With the implementation of restrictions on community activities and the need for social distancing, consumers have increasingly turned to online platforms for various services, including food delivery. In this regard, understanding the factors that influence customer loyalty in the context of online food delivery becomes crucial. The aim of this study was to examine the impact of service quality, price, and promotion on ShopeeFood customer loyalty among students from the Faculty of Economics and Business at Makassar State University, both individually and collectively. To achieve this aim, a sample of 100 students from the Faculty of Economics and Business was selected based on predetermined criteria. Data collection techniques, including questionnaires, interviews, and a literature review, were employed. The collected data were analyzed through validity and reliability tests, as well as the classical assumption test, comprising normality, multicollinearity, and heteroscedasticity tests. Multiple linear analysis, hypothesis testing, and the coefficient of determination were also conducted to examine the relationships between the variables and customer loyalty. The study revealed that service quality, price, and promotion all played significant roles in influencing customer loyalty. Service quality has a significant impact on customer loyalty. Price plays a significant role in customer loyalty. Promotions have a significant influence on customer loyalty. Overall, service quality, price, and promotion collectively affect customer loyalty.